The Mediating Role of Patient Activation on the Relationship Between Social Support and Health-Promoting Behavior in Patients with Thyroid Cancer: A Cross-Sectional Study - Li P; Li Y; He C; Wang H; Yin X; Jiang Y; Yin T (Journal of Multidisciplinary Healthcare)
Pin Li,1 Yongheng Li,1 Caiyun He,2 Hengxu Wang,3 Xiaomin Yin,4 Yuanyuan Jiang,2 Tao Yin1 1Department of Nursing, The Fourth Hospital of Changsha (Integrated Traditional Chinese and Western Medicine Hospital of Changsha, Changsha Hospital of Hunan Normal University), Changsha, 410006, People’s Republic of China; 2School of Nursing, Department of Medicine, Hunan Normal University, Changsha, 410013, People’s Republic of China; 3School of Nursing, Changsha Medical University, Changsha, 410219, People’s Republic of China; 4General Surgery Ward I, The Fourth Hospital of Changsha (Integrated Traditional Chinese and Western Medicine Hospital of Changsha, Changsha Hospital of Hunan Normal University), Changsha, 410006, People’s Republic of ChinaCorrespondence: Tao Yin, Department of Nursing, The Fourth Hospital of Changsha City, No. 70, Lushan South Road, Yuelu District, Changsha, 410006, People’s Republic of China, Tel +86 15873151720, Email 328220331@qq.comPurpose: This study aimed to explore social support on health promotion behavior among patient with thyroid cancer and to investigate the mediating effect of patient activation in this relationship.Participants and Methods: This study used a cross-sectional correlational design. A convenience sample of 618 thyroid cancer patients from two hospitals in Hunan Province, China, was included in the study. Data were collected from April to November 2023. The survey tools include: the General Information Questionnaire, Patient Activation Scale, Health Promoting Lifestyle Scale Chinese Revised Version, Social Support Rating Scale. Structural equation modeling and bootstrapping were used to analyze the mediating effect of patient activation on social support and health promotion behavior.Results: Social support was positively correlated with health promotion behavior (r= 0.360, P< 0.001), social support was positively correlated with patient activation (r=0.293, P< 0.001), patient activation was positively correlated with health promotion behavior (r=0.541, P< 0.001). Patient activation partially mediated the impact of social support and health promotion behavior, accounting for 33.03% of the total effect.Conclusion: Thyroid cancer patients’ health behavior need to be improved. Medical professionals ought to devise an intervention strategy based on pathways that influence health promotion behaviors among thyroid cancer patients. This approach aims to improve social support and patient activation, in order to promote the improvement of health promotion behavior, ultimately reducing the burden of medical care.Keywords: thyroid cancer, health-promoting behavior, patient activation, social support, health promotion